Histopathology of the muscle in rheumatic diseases - S. Barsotti; A. Tripoli; L.E. Pollina; M. Mosca; R. Neri (PAGEPress Publications, 2018)
The presence of muscular symptoms is common in rheumatological clinical practice, but often the differential diagnosis between muscular involvement in connective tissue diseases, vasculitis and drug-induced myopathy may be difficult. In addition to clinical assessment, laboratory analysis and instrumental examinations, muscle biopsy may help to clarify the diagnosis in patients with muscular involvement. The purpose of this review is to provide a critical analysis of the current medical literature on muscular histopathology, to help clinicians to identify when to perform muscular biopsy and to provide a practical guide to a better understanding of the pathology report. Moreover, we provide an overview of the muscular involvement and the most common histopathological findings in rheumatic diseases.